(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The Britishfiction is an important part of English literature. This article focuses onnovels, written in English, by novelists who were born or have spent a significant part oftheir lives in England, or Scotland, or Wales, or NorthernIreland (or Ireland before 1922)]. However, given the nature of thesubject, this guideline has been applied with common sense, and reference ismade to novels in other languages or novelists who are not primarily Britishwhere appropriate.